High Serum Stability of Collagen Hybridizing Peptides and Their Fluorophore Conjugates - Bennink, Lucas L. (Mol Pharm, 2017)
Collagen hybridizing peptides (CHPs) have a great potential for use in targeted drug delivery, diagnostics, and regenerative medicine due to their ability to specifically bind to denatured collagens associated with many pathologic conditions. Since peptides generally suffer from poor enzymatic stability, resulting in rapid degradation and elimination in vivo, CHP’s serum stability is a critical parameter that may dictate its pharmacokinetic behavior. Here, we report the serum stability of a series of monomeric CHP derivatives and establish how peptide length, amino acid composition, terminal modification, and linker chemistry influence their availability in serum. We show that monomeric CHPs comprised of the collagen-like Gly-Pro-Hyp motif are resistant to common serum proteinases and that their stability can be further increased by simple N-terminal labeling which negates CHP’s susceptibility to proline-specific exopeptidases. When fluorescent dyes are conjugated to a CHP via maleimide–thiol reaction, the dye can transfer from CHP onto serum proteins (e.g., albumin), resulting in an unexpected drop in signal during serum stability assays and off-target accumulation during in vivo tests. This work is the crucial first step toward understanding the pharmacokinetic behavior of CHPs, which can facilitate the development of CHP-based theranostics.